2011
DOI: 10.1016/j.nucmedbio.2011.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chelator conjugation level and injection dose on tumor and organ uptake of 111In-labeled MORAb-009, an anti-mesothelin antibody

Abstract: Introduction Radiolabeling of a monoclonal antibody (mAb) with a metallic radionuclide requires the conjugation of a bifunctional chelator to the mAb. The conjugation, however, can alter the physical and immunological properties of the mAb, consequently affecting its tumor targeting pharmacokinetics. In this study, we investigated the effect of the amount of 2-(p-isothiocyanatobenzyl)-cyclohexyl-diethylenetriamine-pentaacetic acid (CHX-A″) conjugated to MORAb-009, a mAb directed against mesothelin and the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 20 publications
2
30
0
Order By: Relevance
“…The BD and PET imaging studies of 64 Cu-amatuximab in a mouse model of A431/H9 tumors demonstrated that the tumor uptake and blood retention of 64 Cu-amatuximab was inversely proportional to the tumor size whereas the liver uptake was positively correlated to the tumor size (Fig.2), similar to the results obtained previously with 111 In-amatuximab using A431/K5 tumors [14]. The PET imaging and uptake data from the ROI analysis of the images best illustrated the effect of amatuximab dose (2 vs. 60 μg) on the blood retention and the uptake of 64 Cu-amatuximab in tumor and major organs (Fig.4).…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…The BD and PET imaging studies of 64 Cu-amatuximab in a mouse model of A431/H9 tumors demonstrated that the tumor uptake and blood retention of 64 Cu-amatuximab was inversely proportional to the tumor size whereas the liver uptake was positively correlated to the tumor size (Fig.2), similar to the results obtained previously with 111 In-amatuximab using A431/K5 tumors [14]. The PET imaging and uptake data from the ROI analysis of the images best illustrated the effect of amatuximab dose (2 vs. 60 μg) on the blood retention and the uptake of 64 Cu-amatuximab in tumor and major organs (Fig.4).…”
Section: Discussionsupporting
confidence: 85%
“…Since shed mesothelin can act as a decoy preventing anti-mesothelin antibodies from targeting mesothelin-expressing tumors, we undertook our current research to find an optimum dose of amatuximab to neutralize the shed mesothelin and improve the tumor uptake of the antibody. We found in a nude mouse model of A431/K5 tumor (mesothelin-positive human epidermoid carcinoma cells) that the tumor uptake and blood retention of 111 In labeled amatuximab was inversely correlated to the tumor size, whereas the liver and spleen uptakes showed a positive correlation with tumor size [14]. However, we did not correlate the tumor and major organ uptakes with the concentration of circulating shed mesothelin since no methods to determine the shed mesothelin were available at the time the study of 111 In-labeled amatuximab was performed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…By recognizing the existence and extent of heterogeneity, PET imaging of a tumor-specific target adds valuable information for individualized treatment decisions. (45)(46)(47)(48). Moreover, an antibody targeting MSLN was recently conjugated to quantum dots encapsulated in micelles to detect human tumor xenografts in mice (49).…”
Section: Discussionmentioning
confidence: 99%